The power of Hindu’s local wisdom in maintaining financial performance of Jempiring female farmers group in Badung regency during COVID-19 pandemic - Sunariani, Ni Nyoman; Suryathi, Ni Wayan; Wijayanti, Ni Wayan; Sumantri, I G. A. N. Alit; Sudama, I Ketut; Sukarnasih, Desak Made; Bagus, Anak Agung Gede (International research journal of management, IT and social sciences, 2021)
The purpose of this study was to analyze the power of Hindu’s local wisdom in maintaining the financial performance of the group of of Jempiring female farmers in Badung Regency during the COVID-19 pandemic. The research method uses primary and secondary data sources, the type of data used is quantitative data and qualitative data, data collection techniques are carried out by in-depth interviews and documentation studies, and then data analysis techniques are carried out using quantitative and qualitative analysis. The results of this study indicate that the power of Hindu’s local wisdom, Tri Hita Karana, turned out to be able to maintain the financial performance of the group of Jempiring female farmers in Badung Regency during the COVID-19 pandemic, both in terms of liquidity, solvency, and from the side of profitability. So that the ability to pay debts, both short-term debt and long-term debt, can still be done. This was reinforced because of the confidence of members of the group of Jempiring female farmers in implementing local wisdom Tri Hita Karana that the obligation to pay debt must still be prioritized so that this group still remained at the time of the COVID-19 pandemic situation.